Spectromicroscopy of Nanoscale Materials in the Tender X‐Ray Regime Enabled by a High Efficient Multilayer‐Based Grating Monochromator. Issue 1 (29th November 2022) - Werner, Stephan; Guttmann, Peter; Siewert, Frank; Sokolov, Andrey; Mast, Matthias; Huang, Qiushi; Feng, Yufei; Li, Tongzhou; Senf, Friedmar; Follath, Rolf; Liao, Zhohngquan; Kutukova, Kristina; et al.
Abstract: The combination of near edge X‐ray absorption spectroscopy with nanoscale X‐ray imaging is a powerful analytical tool for many applications in energy technologies, catalysis, which are critical to combat climate change, as well as microelectronics and life science. Materials from these scientific areas often contain key elements, such as Si, P, S, Y, Zr, Nb, and Mo as well as lanthanides, whose X‐ray absorption edges lie in the so‐called tender photon energy range 1.5–5.0 keV. Neither conventional grazing incidence grating nor crystal monochromators have high transmission in this energy range, thereby yielding the tender photon energy gap. To close this gap, a monochromator setup based on a multilayer coated blazed plane grating and plane mirror is devised. The measurements show that this novel concept improves the photon flux in the tender X‐ray regime by two‐orders‐of‐magnitude enabling previously unattainable laboratory and synchrotron‐based studies. This setup is applied to perform nanoscale spectromicroscopy studies. The high photon flux provides sufficient sensitivity to obtain the electronic structure of Mo in platinum‐free MoNi4 nanoparticles for electrochemical energy conversion. Additionally, it is shown that the chemical bonding of nano‐structures in integrated circuits can be distinguished by the electronic configuration at the Si‐K edge. Abstract : The tender X‐ray photon energy range plays an important role for the understanding of mechanism in modern catalytic and energy storage devices. A novel monochromator setup is reported that is 100 multi more efficient than conventional solutions in the tender X‐ray range, and therefore permits the determination of electronic states of hierarchically nanostructured materials from both energy technologies and microelectronics.